Narrow-linewidth double-peak figure-eight passively mode-locked fiber laser. (18th May 2015) - Liu, Xianglian; Li, Xiaohui; Zhang, Wei; Wang, Yishan
Abstract: We report on the experimental observation of narrow-linewidth double-peak dissipative solitons in a figure-eight Yb-doped passively mode-locked fiber laser in the large net normal cavity dispersion regime. Without any physical bandpass filters in the cavity, stable mode-locking pulses with a duration of 416 ps and a 3 dB bandwidth of 0.3 nm can be directly generated from the laser cavity. The edge-to-edge bandwidth of the spectrum is about 5 nm. The repetition rate of the dissipative solitons is 3.9 MHz. With the increase of pump power, the central wavelength of the dissipative solitons shifts toward a short wavelength and edge-to-edge spectral widths are widened gradually. These phenomena are theoretically explained.